(untitled) (Archive of Conferences, 2021)
Today, our country is going through a period of radical changes in the spiritual and educational sphere, the revival of Islamic enlightenment and culture, especially the spiritual, moral and physical upbringing of young people has risen to the level of state policy. The preservation of our centuries-old national and religious values, the study of the invaluable heritage of our ancestors, who made a great contribution to the development of world science and culture, and the upbringing of young people as perfect human beings provide a stable socio-spiritual environment in society. The works of our ancestors, who contributed to the development of Islam and world civilization, have not lost their relevance.